2019
DOI: 10.3390/molecules24152842
|View full text |Cite
|
Sign up to set email alerts
|

Green Extraction of Phenolic Acids from Artemisia argyi Leaves by Tailor-Made Ternary Deep Eutectic Solvents

Abstract: The Artemisia argyi leaf (AL) has been used as a traditional medicine and food supplement in China and other Asian countries for hundreds of years. Phytochemical studies disclosed that AL contains various bioactive constituents. Among bioactive constituents, phenolic acids have been recognized as the main active compounds in AL. To the best of our knowledge, no research has been focused on extraction method for the bioactive phenolic acids from AL. Nowadays, deep eutectic solvents (DESs) are emerging as a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Recently, Duan et al. reported the use of deep eutectic solvent for caffeoyl quinic acids extraction [57] . Derivatives of caffeic acid were extracted from numerous plants leading to various pharmaceutical and cosmetic applications [58–60]…”
Section: Recovery From Agricultural By‐productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Duan et al. reported the use of deep eutectic solvent for caffeoyl quinic acids extraction [57] . Derivatives of caffeic acid were extracted from numerous plants leading to various pharmaceutical and cosmetic applications [58–60]…”
Section: Recovery From Agricultural By‐productsmentioning
confidence: 99%
“…Recently, Duan et al reported the use of deep eutectic solvent for caffeoyl quinic acids extraction. [57] Derivatives of caffeic acid were extracted from numerous plants leading to various pharmaceutical and cosmetic applications. [58][59][60] As these extracts already exhibit interesting properties, few works were dedicated to specific recovery of pure caffeic acid.…”
Section: State Of the Artmentioning
confidence: 99%
“…In recent years, DESs have been proved to be efficient solvents to extract natural products such as flavonoids [46][47][48], isoflavonoids [49], phenolic compounds [2], phenolic acids [50], terpenoids [18], and alkaloids [51,52] from plant materials. As a new type of green extractant, effective extraction of hazard residues by DESs is critical to ensuring the environment and consumer safety.…”
Section: Deep Eutectic Solvents As the Alternative Extraction Solventmentioning
confidence: 99%
“…This Special Issue has received remarkably positive feedback, with many contributions submitted by numerous geographically diverse scientists, resulting in a collection of 10 publications, including two exhaustive review articles [9][10][11][12][13][14][15][16][17][18]. Among the contributing authors, authors can be found from Asia (China, India, and Uzbekistan), Europe (Spain), South America (Brazil and Chile) and North America (Mexico).…”
mentioning
confidence: 99%
“…The Artemisia argyi leaf has been used as a traditional medicine and food supplement in Asian countries for hundreds of years. Phytochemical studies disclosed that Artemisia argyi leaf contains various bioactive constituents, mainly phenolic acids, which have great potential as possible alternatives to those organic solvents in health-related areas such as food and pharmaceuticals [14]. Regarding the use of seaweeds as alternative dietary fibre sources to terrestrial vegetables, in this Special Issue an article is presented evaluating the nutritional composition and physicochemical properties of two dried commercially interesting edible red seaweeds, Gracilaria corticata and G. edulis.…”
mentioning
confidence: 99%